PROSES PENYIDIKAN ANAK PELAKU TINDAK PENGANIAYAAN YANG MENGAKIBATKAN KEMATIAN BERDASARKAN UU NO.11 TAHUN 2012: The Process of Investigation Into Juvenile Persecution Resulting in One’s Demised Based on Law Number 11 of 2012 - Permatasari, Astri Ratna; Saragih, Effendy (AMICUS CURIAE, 2024)
The important role of kids as part of defending the life of the nation and state requires the government's awareness to guarantee the right to life of every child. Children need to be protected against all conditions and circumstances, including Juvenile Criminal Justice which they are not familiar with. The difference between the Juvenile Criminal Justice system and adult justice requires certain requirements for law enforcers within it. Juvenile justice involves direct or indirect investigators, child public prosecutors, and juvenile judges in court proceedings. The handling of cases of children who commit criminal acts is regulated in Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. The results of this study are (1) The process of investigating children who are perpetrators of abuse resulting in death according to Law Number 11 of 2012 at the Tangerang City Police; (2) There are obstacles in the process of investigating children as perpetrators of abuse resulting in death at the Tangerang City Police.